How do you find (fog)(10)(fog)(10) given f(x)=-9x-9f(x)=9x9 and g(x)=sqrt(x-9)g(x)=x9?

1 Answer
Apr 12, 2017

color(red)(-18)18

Explanation:

(fog)(x)(fog)(x) basically means f(g(x))f(g(x)) i.e.i.e. a function obtained by substituting g(x)g(x) in place of xx in f(x)f(x).

hence in this case,

(fog)(x) = f(g(x)) = -9*g(x) - 9(fog)(x)=f(g(x))=9g(x)9
= -9*sqrt(x-9) - 9 = -9sqrt(x-9)-9=9x99=9x99

therefore (fog)(10) = f(g(10)) = -9sqrt(10-9)-9
= -9*1-9 = -9-9 = color(red)(-18)

Another way to do it would have been to first find g(10) ant then substitute the value obtained into f(x).
therefore g(10) = sqrt(10-9) = color(red)1
therefore f(1) = -9*1-9 = 9-9 = color(red)(-18)